Properties of Cast Iron Produced with a Limited Share of Pig Iron in the Charge - Krzysztof Janerka; Jan Jezierski (Crystals)
The article presents issues related to the melting of cast iron with a limited or zero share of pig iron in the charge. The results of melts conducted in electric induction furnaces are presented. The elimination of pig iron and its replacement with steel or return scrap is highly significant in the context of sustainable production and product life cycle assessment (LCA). The paper presents the results of research carried out during melts conducted under both laboratory and industrial conditions. The chemical composition of the cast iron, its physicochemical properties obtained from the analysis of the cooling curve and its derivative, as well as the structure, were analyzed. It was found that cast iron produced using high-quality steel scrap contains fewer sulfur and phosphorus impurities. However, it was also observed that such cast iron exhibits reduced nucleation ability, which can be improved by applying an inoculation process.